Towarzystwo Chowu Drobiu i Królików w Jarosławiu jako przejaw XIX-wiecznego nowoczesnego polskiego rolnictwa - Domarańczyk, Daria (Zeszyty Wiejskie, 2014)
The article is the oldest Polish ornithological organization, which was founded in 1894 in Yaroslavl efforts of the princely couple – Mary and Jerzy Czartoryski. Rearing and Rabbit Society (formerly Ornithological Society) had to act based on existing in Galicia legislation which, although enjoyed the greatest freedom of Polish territories under occupation, it had its limitations. In addition, it was very progressive by adopting in their ranks as women. The organization brings together breeders of pedigree poultry and rabbits. For organized meetings, conferences and exhibitions exchanged the latest news on this subject, presented a new breed of animal, and so shown. demonstration chicken coops. The news article – mainly reports come from showing up in Lviv in the years 1895–1897 the biweekly "Ster". Its founder and editor-in-chief was a charismatic emancipated Paulina Kuczalska-Reinschmit. The text was also endorsed with extensive commentary on the legal ability to function in Galicia Polish organizations and associations.